Construction of carbon-nickel cobalt sulphide hetero-structured arrays on nickel foam for high performance asymmetric supercapacitors. (20th August 2015) - Wang, Hai; Wang, Chong; Qing, Chen; Sun, Daming; Wang, Bixiao; Qu, Gan; Sun, Miao; Tang, Yiwen
Graphical abstract: Abstract: NiCo2 S4 and carbon-NiCo2 S4 hetero-structured nanosheet arrays have been firstly synthesized on nickel foams in a facile hydrothermal and CVD method. The products NiCo2 S4 and carbon-NiCo2 S4 are obtained in Na2 S aqueous solution in a hydrothermal reaction from precursor of NiCox (OH)y and carbon-NiCo2 O4 through anion exchange respectively, which are characterized by XRD, TEM, Raman analysis. The obtained binary metal sulphide NiCo2 S4 nanosheet delivers better electrochemical activity and higher mass loading compared with NiCo2 O4 . In addition, carbon introduced enhances the capacitive behaviours and cycle performance for enhanced electric conductivity and stable architecture. The integrated carbon-NiCo2 S4 electrode exhibits high areal capacitance of 8.33 F cm −2 and ultrahigh specific capacitance of 1893.2 F g −1 with a potential window of 0.8 V and high mass loading of 4.4 mg cm −2 and good cycle performance in a three-electrode system. The asymmetric supercapacitor is further assembled using carbon-NiCo2 S4 as the positive electrode and activated carbon as the negative electrode. The integrated asymmetric supercapacitor demonstrates a high energy density of 68.82 Wh kg −1 at a power density of 47.83 W kg −1, which confirms its practical applicability.